2022
DOI: 10.1017/s0950268822001601
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 seroepidemiology in paediatric population during Delta and Omicron predominance

Abstract: Limited prospective SARS-CoV-2 data in children regarding the impact of Omicron variant in seropositivity have been reported. We investigated SARS-CoV-2 seropositivity in children between 1 September 2021 and 30 April 2022, representing Delta and Omicron predominance periods. Serum samples from children admitted to the major tertiary Greek pediatric hospital for any cause, except for COVID-19, were randomly collected and tested for SARS-CoV-2 natural infection antibodies against nucleocapsid antigen (Elecsys® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…2 . This is similar to the findings of other studies, which found that antibodies attributed to natural SARS-CoV-2 infection had a detectable high seropositive rate during the Omicron wave 23 , 33 35 . This positivity rate did not show any significant differences by sex or occupation.…”
Section: Discussionsupporting
confidence: 92%
“…2 . This is similar to the findings of other studies, which found that antibodies attributed to natural SARS-CoV-2 infection had a detectable high seropositive rate during the Omicron wave 23 , 33 35 . This positivity rate did not show any significant differences by sex or occupation.…”
Section: Discussionsupporting
confidence: 92%
“…In pediatric population, SARS-CoV-2 seropositivity increased during Omicron variant period compared with Delta waves, implicating either increased transmissibility or reinfection rates [43]. For children with native livers, the severance of the infection was usually milder and there was no significant difference in the risk of hospitalization for young children between Omicron and Delta Newly-onset LT complication None None None None None [44].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing SARS-CoV-2 immunity, either as a result of natural infection or vaccination in children, seems to play a crucial role in MIS-C pathogenesis and severity. According to CDC, SARS-CoV-2 seroprevalence attributed only to infection-induced immunity has reached 92% in children by March 2023, while a significant increase in seropositivity during Omicron compared to Delta variant in the pediatric population has also been observed in Europe as well [ 20 ]. However, SARS-CoV-2 vaccination has also affected MIS-C incidence.…”
Section: Incidence Of Mis-cmentioning
confidence: 99%